Performance analysis for wintering pattern in Hevea brasiliensis clones - Vinod K K; Krishnakumar A K; Meenattoor J R; Pothen J; Sethuraj M R (Indian Journal of Natural Rubber Research, 1996)
A study was undertaken to group rubber (Hevea brasiliensis) clones based on their wintering behaviour in Tripura, one of the rubber growing areas of North East India. Fifteen clones from a clone evaluation trial were scored for the wintering pattern at weekly intervals for six weeks from December to Fubruary during 1988-89, 1989-90 and 1991-92 period. Wintering pattern of clones was uniform for all the years under study. Mean weekly scores were used for clustering process. Three distinct clusters of early, intermediate and late wintering clones were obtained viz, (i) RRII 105 and RRIC 105, (ii) RRIM 600, PB 86, GT 1, RRIC 52 and PB 235 and (iii) RRII 118, RRIM 605, GI 1, Harbel 1, RRII 5, PB 5/51 and RRIM 703. The remaining clone, RRII 203, was found to fall in between the second and the third clusters. The results can be used in characterising clones as well as selecting clones for establishing polyclonal breeding gardens.
Keywords: Cluster analysis; Hevea brasiliensis; Tripura; Wintering